Impact on Indoor Air of Multifunctional Materials Made with Animal Waste and Agro-Industrial By-Products - Vasilica Vasile; Irina Popa; Cristian Petcu; Alina Dima; Mihaela Ion (Chemistry Proceedings)
One severe public health problem globally is air pollution, as exposure to air pollutants threatens the health of people everywhere in the world. Agriculture generates waste, the improper disposal of such waste producing adverse environmental effects like air pollution, etc. In this context, our research focused on capitalizing on animal waste (wool) and agro-industrial by-products (sunflower seed husks) as additives in two types of aqueous dispersion finishing/protection products, serving as binders. The paper presents the results from the monitoring of volatile organic compounds (VOCs) emissions of four types of innovative multi-layer finishes made with such types of waste.